Low-cost rental apartments as an alternative to the Kampung Improvement Program : an evaluation of the Dupak Pilot Project in Surabaya, Indonesia - Anindito, Raphael M.; Yap, Kioe Sheng; K.ammeier, H. Detlef; Lefebvre, Bernard G.; Canadian International Development Agency (CIDA) (Bangkok : Asian Institute of Technology, 1992)
Although kampung improveme nt program has been successful in rnany cities in Indonesia, it can not be app lied in all circumstances. Two obstacl es t o kampung improvement are very p oor environment condition in the kampung that ma ke upgra ding impossible, and a l arge number of house renters who will not invest in housing. The dupak pilot project has been designed in response to the problem. In the Dupak project the residents of the kampung have been resettled in apartme nts on site The objective of this evaluation is to assess the potential of rental apartment as an altern ative for KIP. The quasi experimental method i s use in t his evaluation. Fifty percent of the households in the apartment or 7 3 respondent were taken as the target group. Seventy Respondents from the household in the s urrounding are were take as t he control group. I t is found that most of the project objectives have been achieved; the p hysical improveme nt, institutional developme nt and conservation of the social condition. The objectives t h at were not f ully achieve are the conservation of the economic activity and the accommodation of t he original residents. There is no significant gentrification, al though a l.most hal f of t he original population has been displace. The average rent has not increased more than normal, but t he l owest rents have increased significantly. The income growth of the original resident is unaffected by this project. Expenditures for water and e l ectricity have decreased significantly. For the main renters and ' rent-lords', the rental apartment are better than any other possible option. For the secondary renters, specially those with l owe r incomes the rental apartments are still unfavorable . Although the rental apartments offer some benefits for t he government and soci ety, the conseque nces are still unaffordable. For t he government as the developer the rental apartment is not a viable option. A better alternative for KIP is still needed Instead of being a repl acement for KIP, rental apartments are a s uppleme nt for KIP and the urban housing s upply . The rental apartme nts option can only be use under some particular conditions.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology
Keywords: Apartment houses -- Indonesia -- Surabaya